2006
DOI: 10.1002/cncr.21926
|View full text |Cite
|
Sign up to set email alerts
|

Radical prostatectomy for clinical T4 prostate cancer

Abstract: Paravalvular leakage following the atrioventricular valve replacement, though mostly harmless with insignificant morbidity, can result in heart failure and significant hemolysis that requires treatment. Reoperation is still the treatment of choice, but there is a high risk of recurrence, especially in patients with a history of endocarditis and/or those who have already undergone reoperation for paravalvular leakage. Recently, percutaneous closure of perivalvular leaks with occluders or coils have become an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 15 publications
0
48
1
7
Order By: Relevance
“…Recently, Johnstone et al [3] reported that radical prostatectomy with or without hormone therapy appeared to have a survival benefit, especially in cT4 PCa patients with positive regional lymph node compared to those with negative lymph node status. Messing et al [11] reported that immediate hormone therapy after radical prostatectomy and pelvic lymphadenectomy improved 5-year cause-specific survival by about 15% in patients with node-positive PCa, although the study targeted patients with cT2 disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Johnstone et al [3] reported that radical prostatectomy with or without hormone therapy appeared to have a survival benefit, especially in cT4 PCa patients with positive regional lymph node compared to those with negative lymph node status. Messing et al [11] reported that immediate hormone therapy after radical prostatectomy and pelvic lymphadenectomy improved 5-year cause-specific survival by about 15% in patients with node-positive PCa, although the study targeted patients with cT2 disease.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that cystoprostatectomy for primary cT4 tumor provided effective and durable palliation of lower urinary tract symptoms (LUTS). Recent data from the Surveillance Epidemiology and End Results (SEER) revealed that patients who underwent radical prostatectomy for cT4 PCa had increased survival compared with patients who received radiation therapy alone or hormone therapy alone and had a survival comparable to that of patients who received combined therapy of radiation and hormone therapy [3] . Furthermore, the study indicated the survival of radical prostatectomy over combined radiation therapy with hormonal therapy for cT4 PCa with lymph node metastases [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is only one study based on SEER data on RRP in cT4 prostate cancer [12]. Survival rates at 1, 3 and Months after radical prostatectomy Overall survival estimate 5 years were lowest among patients who received no treatment and highest among those who had RRP.…”
Section: Discussionmentioning
confidence: 98%
“…There are few data published on radical retropubic prostatectomy (RRP) in nonmetastatic prostate carcinoma, which histologically shows neoplastic cells among smooth muscle bundles of the bladder neck [6][7][8][9][10][11]. Indeed, only one publication, based on data from the register of Surveillance Epidemiology and End Results (SEER), has broached the feasibility of radical surgery in clinical T4 prostate cancer [12].…”
Section: Introductionmentioning
confidence: 99%